Discourse on the Success of the Indonesian Men's Basketball Team at the 2022 SEA Games - Putranto, Teguh Dwi; Alvin, Silvanus; Asmarantika, Rossalyn (Journal Communication Spectrum: Capturing New Perspectives in Communication, 2024)
From its initial participation in the SEA Games in 1977 to 2019, the Indonesian men's basketball team has never won a gold medal. Before the 2022 SEA Games, Indonesia created history by becoming the first country to win a gold medal. This study aims to understand better the conversation surrounding the 2022 Southeast Asian Games men's basketball team. This qualitative study employs Van Dijk's critical discourse analysis method. The study's analysis unit is online news on Mainbasket.com from April 1 to May 29, 2022. The finding of this study demonstrates that the conversation in the online news outlet "Mainbasket" has picked up signs of apprehension among the Indonesian basketball team ahead of the 2022 SEA Games in Vietnam. Mainbasket also highlights the four leading players of the Indonesian national basketball team. Mainbasket also appreciated the athletes for winning the first gold medal in Indonesian basketball. In addition, this victory is only considered a stepping stone towards the FIBA ASIA Cup 2022 and leads to a match at the FIBA World Cup 2023. To cite this article (7th APA style): Putranto, T. D., Alvin, S., & Asmarantika, R. (2024). Discourse on the success of the Indonesian Men's Basketball Team at the 2022 SEA Games. Journal Communication Spectrum: Capturing New Perspectives in Communication 14(1), 11-27. https://doi.org/10.36782/jcs.v14i1.2426